Prawa człowieka w kontekstach kulturowych - Przybyszewski, Krzysztof (Wydawnictwo Naukowe Instytutu Filozofii UAM, 2010)
The power of human rights idea and its expansion are connected with the experience of so far unprecedented pain and cruelty caused by man to man during the Second World War. Doctrine of legal positivism strenghtened totalitarian systems. One of the essential goals that were set by totalitarian systems was ethnic cleansing within both one’s and subjugated communities. To achieve this goal, concentration camps were established. This Second World War’s events gave raise to a question: does the common morality of the whole mankind exist? The Nuremberg Trials based on conviction that this common morality of the whole mankind exists. In this lawsuits Nazis were on trials for mass murder and crimes against humanity despite the fact that this crimes did not exist as a criminal offences in international law of that time. Lawyers of Nazis argued that their clients should not have been on trials for crimes against humanity because the rule “lex retro non agit” (“the law does not operate retroactively”) should have been in force. International Military Tribunal dismissed this argument – it was stated they tried Nazis are responsible for acts resulting from breach of the natural law. Therefore, the primacy of natural law over civil law (was approved and they admitted that morality and law are essential components of international reality. Since The Nuremberg Trials, the process of making international relations more ethical proceeded consistently through positivisationi.e. introducing human rights ideas to civil law (this issue is included in the Part I of the book: Positivisation of human rights idea). In this way, contemporary human rights as civil law arose, established on the basis of international agreement. Using them in order to legitimize and validate humanitarian interventions undertaken in various parts of the world became the common standard. However, positivisation of human rights idea did not mean that one common paradigm was accepted. Many interpretation of human rights arose and many new human rights formed in concrete cultures. It gives raise to a question about validity of interventions especially in the context of cultural differences in various parts of the world that influence perception, understanding and interpretation of human rights (this issues are discussed in Part II of this book). At present human rights are not only relativized to cultural contexts but undergo semantic changes as a result of globalisation process as well (Part II of the book: Human rights idea vs globalisation). Moreover, the propositions of establishing institutions and global structures that would strengthen human rights idea appear, interalia new propositions of citizenship defining (ujmowanie jako definiowanie)in response to a decreasing role and significance of nation states in the age of globalization. The idea of human rights dominated present-day law, culture and daily life both in local and global dimension. Human rights issue became essential for philosophy, especially political philosophy.
Keywords: fundamental rights; human rights; globalisation; islam; confucianism; animism; Hinduism; human dignity